Heavy Metal Contain Cu and Cd on the Mullet in the estuary of Donan River, Cilacap, Central Java - Yudha Prastyo; Djamar T.F Lumban Batu; Sulistiono Sulistiono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
The estuary of Donan River is an aquatic area that commonly utilized for some activities such as industrial, fisheries and domestic activities. The effluents of many activities may be cause heavy metal contamination for water enivornemant and organism live in the water. The aim of this research was to analyse heavy metal contain Cu and Cd on the mullet (Chelon subviridis) muscle caught at estuary of Donan River, and to determine the safety limit for community consumption. Sampling had been carried out for 6 months, from August 2015 to January 2016. Heavy metal concentration was measured by AAS (Atomic Absorption Spectrophotometer). Result of the study shows that heavy metal Cu and Cd in the fish muscle were 0.5009-2.6021 mg/kg and 0.0165-0.2307 mg/kg, respectively that were higher than safety limit. Based on the study, the safety limit for consumption is 151.72 g meat/week (for adult 50 kg body weight) and 45.52g meat/week (for child 15 kg body weight).